Predictive value of Geriatric Nutritional Risk Index for overall survival in maintenance hemodialysis patients - He, He; Yang, Yanlang (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to assess the predictive value of the Geriatric Nutritional Risk Index (GNRI) for overall survival in maintenance hemodialysis (MHD) patients, providing insights into the role of nutritional status in long-term outcomes for this patient population.MethodsA retrospective cohort study was conducted using data from 395 MHD patients treated between 2020 and 2024. The GNRI was calculated for each patient based on their baseline clinical data, including serum albumin, body mass index (BMI), and other relevant parameters. Patients were categorized into different groups according to their GNRI scores. Kaplan–Meier survival analysis was used to compare survival rates among different GNRI groups. Cox proportional hazards regression models were employed to evaluate the association between GNRI and overall survival, adjusting for potential confounding factors such as age, comorbidities, and other clinical indicators. The predictive accuracy of GNRI was further assessed using receiver operating characteristic (ROC) curve analysis.ResultsThe study found that patients with lower GNRI scores had significantly lower overall survival rates compared to those with higher scores. Specifically, patients in the lowest GNRI quartile had a higher mortality risk than those in the highest quartile. The Cox regression analysis showed that GNRI was an independent predictor of overall survival in MHD patients, with a hazard ratio (HR) indicating a substantial increase in mortality risk for each unit decrease in GNRI. The ROC curve analysis demonstrated that GNRI had a good predictive ability for overall survival, with an area under the curve (AUC) of 0.754 (95% CI: 0.7085–0.8064) suggesting its potential as a useful prognostic tool. At the optimal cut-off value of 93, the sensitivity was 78.2% and the specificity was 68.5%.ConclusionThe Geriatric Nutritional Risk Index (GNRI) is a valuable and reliable predictor of overall survival in maintenance hemodialysis patients. Its incorporation into routine clinical practice may help identify high-risk patients who require more intensive nutritional support and improve their long-term prognosis.